A Pengaruh Model Project Based Learning Terhadap Sikap Gotong Royong Siswa Sekolah Dasar (Universitas Dr. Soetomo, 2023)
Abstract The attitude of cooperation is very important to be instilled in students so that students can easily socialize wherever they are. The attitude of cooperation is a self-aware attitude from each individual to help ease the burden on other individuals. The cooperation attitude has the characteristics of mutual care, cooperation, democracy, discussion, mutual help, habituation of consensus deliberation, empathy, solidarity, loyal friends, and volunteerism. In group learning after the Covid-19 pandemic, the students' cooperation attitude began to weaken. Several indicators of a weakened cooperation attitude were collaboration, caring, and sharing. According to the teacher, the weakening of this cooperation attitude is because students are used to learning independently at home, so students feel they can do their work without the help of their friends. Thus, this research aims to show the difference in the attitude of cooperation between those who use the project-based learning model and the conventional learning model of elementary school students. The data in this study were obtained from the results of the students' post-response which were analyzed using an independent sample t-test. The results of the post-response show that there is a very significant difference in the attitude of cooperation between those who use the project-based learning model and those who use conventional learning models of elementary school students. This difference can be seen from the post-response results of the experimental class which applies the project-based learning model which is higher than the control class which applies the conventional learning model. Keywords: project based learning model, mutual cooperation attitude, elementary school Abstrak Sikap gotong royong sangat penting ditanamkan didalam diri siswa agar siswa dapat mudah bersosialisasi dimanapun mereka berada. Sikap gotong royong adalah sebuah sikap sadar diri dari masing-masing individu untuk membantu meringankan beban individu lain. Sikap gotong royong memiliki karakteristik saling peduli, bekerja sama, demokratis, diskusi, saling membantu, pembiasaan musyawarah mufakat, empati, solidaritas, setia kawan, dan kerelawanan. Dalam pembelajaran berkelompok setelah masa pandemi covid-19 saat ini sikap gotong royong siswa mulai melemah, Beberapa indikator sikap gotong royong yang melemah adalah kolaborasi, kepedulian, dan berbagi. menurut guru melemahnya sikap gotong royong ini dikarenakan siswa terbiasa belajar secara mandiri dirumah, sehingga siswa merasa dapat mengerjakan tugasnya sendiri tanpa dibantu oleh temannya. Dengan demikian, tujuan dari penelitian ini adalah untuk menunjukan perbedaan sikap gotong royong antara yang menggunakan model project-based learning dan model pembelajaran konvensional siswa sekolah dasar. Data pada penelitian ini didapatkan dari hasil post-response siswa yang dianalisis menggunakan uji independent sampel t test. Hasil dari post-response menunjukan terdapat perbedaan yang sangat signifikan sikap gotong royong antara yang menggunakan model project-based learning dengan yang menggunakan model pembelajaran konvensional siswa sekolah dasar. Perbedaan ini terlihat dari hasil post-response kelas eksperimen yang menerapkan model project-based learning lebih tinggi dibandingkan kelas kontrol yang menerapkan model pembelajaran konvensional. Kata Kunci: model project based learning, sikap gotong royong, sekolah dasar